TINJAUAN HUKUM PERSPEKTIF ISLAM PADA FENOMENA SERANGAN FAJAR PEMILU SERENTAK 2024 - Abdul Hakam, Sholahuddin; Erwin, Widhiandono; Adimas Wijaya , Putra (Metafora: Education, Social Sciences and Humanities Journal, 2024)
The phenomenon of dawn attacks in the 2024 Simultaneous Elections in Indonesia is in the main spotlight because of the practice of money politics which threatens the integrity and public trust in the democratic process. This research uses a normative juridical approach to analyze the dawn attacks from the perspective of Islamic law and Indonesian positive law. Data was collected through literature studies involving laws, Islamic legal literature, as well as previous research. The results of the research show that the majority of people believe that there are no dawn attacks, although some segments of society still believe in the practice. According to Islamic law, dawn attacks are categorized as haram bribery (risywah), while in Indonesian law, this practice is prohibited under Law Number 7 of 2017 concerning Elections. Analysis shows that strict law enforcement, comprehensive political education, and the use of technology such as e-voting are important steps to eradicate dawn attacks. Active participation from the public, political parties and candidates is very necessary to create fair, transparent and democratic elections. The conclusions of this research emphasize the importance of collaboration between various parties to ensure election integrity and prevent the practice of money politics that undermines democracy. Keywords: Dawn attack, money politics, election integrity, risywah, law enforcement.